CRC Screening Results: Patient Comprehension and Follow-up. (30th January 2019) - Azulay, Revital; Valinsky, Liora; Hershkowitz, Fabienne; Magnezi, Racheli
Background: Fecal occult blood tests are recommended for colorectal cancer screening, but are only effective if colonoscopy follows positive results. Patients with positive results often do not complete follow-up. This study examined the association between patient comprehension and adherence to colonoscopy after positive FIT (Fecal Immunochemical Test). Methods: Five hundred twenty-two patients completed a telephone questionnaire regarding the FIT and its implications 120 days after a positive result. Patients were asked whether they had the test, received the results, and required follow-up. These questions were used to identify the degree to which patients understood medical information. A participant who answered "no" to any question was defined as having "low comprehension" regarding the FIT, and participants who answered "yes" to all 3 questions, as having "high comprehension". Results: Comprehension and colonoscopy adherence were significantly associated. Adherence to colonoscopy was significantly higher among participants with high comprehension, after adjusting for gender, age, education, ethnicity, and socio-economic status. Conclusions: This study demonstrates a link between health comprehension and patient follow-up after positive FIT and contributes to understanding the implications of health comprehension in terms of health promotion. We recommend patients undergoing screening tests receive clear explanations regarding need for follow-up of positive results thus reducing health disparities associated with health comprehension.